Feigning Acute Intermittent Porphyria - Rania Elkhatib; Modupe Idowu; Gregory S. Brown; Yasmeen M. Jaber; Matthew B. Reid; Cheryl Person (Case Reports in Psychiatry)
Acute intermittent porphyria (AIP) is an autosomal dominant genetic defect in heme synthesis. Patients with this illness can have episodic life-threatening attacks characterized by abdominal pain, neurological deficits, and psychiatric symptoms. Feigning this illness has not been reported in the English language literature to date. Here, we report on a patient who presented to the hospital with an acute attack of porphyria requesting opiates. Diligent assessment of extensive prior treatment records revealed thirteen negative tests for AIP.